Transformers : Ghosts of yesterday - Foster, Alan Dean, 1946-; Cian, David (New York : Del Rey/Ballantine Books, 2007)
The national security advisor, confident that the Decepticon threat has been eliminated, makes a fatal mistake when he ignores the cryptic warning, "The fallen shall rise again.".
"The official prequel to the upcoming blockbuster film"--cover.
Adult.
Adult
Keywords: Transformers (Fictitious characters) -- Fiction; Movie novels; Science fiction; Transformers (Fictional characters) -- Fiction; Movie novels; Science fiction